Azilsartan Improves Salt Sensitivity by Modulating the Proximal Tubular Na+-H+ Exchanger-3 in Mice. - Masaki Hatanaka; Jun-Ya Kaimori; Satoko Yamamoto; Isao Matsui; Takayuki Hamano; Yoshitsugu Takabatake; Carolyn M Ecelbarger; Shiro Takahara; Yoshitaka Isaka; Hiromi Rakugi (PLoS ONE, 2016)
A potent angiotensin II type-1 receptor blocker, azilsartan, has been reported to reduce blood pressure more effectively than candesartan. Interestingly, azilsartan can also restore the circadian rhythm of blood pressure. We hypothesized that azilsartan could also improve salt sensitivity; thus, we examined the effect of azilsartan on sodium handling in renal tubules. Subtotal nephrectomized C57BL/6 mice received azilsartan (1.0 mg/kg/day), candesartan (0.3 mg/kg/day), or vehicle via the oral route in conjunction with a normal- (0.3%) or high-salt (8.0%) diet. Two weeks later, the azilsartan group showed significantly lower blood pressure during the light period than the candesartan and vehicle groups (azilsartan: 103.1 ± 1.0; candesartan: 111.7 ± 2.7; vehicle: 125.5 ± 2.5 mmHg; P < 0.05; azilsartan or candesartan vs. vehicle). The azilsartan group also showed higher urinary fractional excretion of sodium during the dark period than the candesartan and vehicle groups (azilsartan: 21.37 ± 3.69%; candesartan: 14.17 ± 1.42%; vehicle: 13.85 ± 5.30%; P < 0.05 azilsartan vs. candesartan or vehicle). A pressure-natriuresis curve demonstrated that azilsartan treatment restored salt sensitivity. Immunofluorescence and western blotting showed lower levels of Na+-H+ exchanger-3 (NHE3) protein (the major sodium transporter in renal proximal tubules) in the azilsartan group, but not in the candesartan or vehicle groups. However, azilsartan did not affect NHE3 transcription levels. Interestingly, we did not observe increased expression of downstream sodium transporters, which would have compensated for the increased flow of sodium and water due to non-absorption by NHE3. We also confirmed the mechanism stated above using cultured opossum kidney proximal tubular cells. Results revealed that a proteasomal inhibitor (but not a lysosomal inhibitor) blocked the azilsartan-induced decrease in NHE3 protein expression, suggesting that azilsartan increases NHE3 ubiquitination. In conclusion, azilsartan (but not candesartan) improved salt sensitivity possibly by decreasing NHE3 expression via ubiquitin-proteasomal degradation.